Profils longitudinaux et ruptures de pente : enseignements géomorphologiques en Bretagne du sud - Jean-Pierre Larue (Physio-Géo)
Analysing of longitudinal profiles of coastal river channels in South Brittany allows to highlight relationships between fluvial dynamics, lithology and tectonics. Profile shapes and knickzones (high gradient sections) show that headward incision is due to tectonics, but controlled by lithology. In little hard rocks, like Brioverian micaschists, profiles are concave- upwards and without any knickzone. While in hard rocks, such as granites or gneiss, large knickzones disrupt the longitudinal profiles. Along the north-south rivers which crosses various lithology,the upstream reaches present longitudinal profiles with high concavity and shallow incision, whereas the downstream reaches are marked by week concavity, important knickzones and deeper incision. This contrast indicates a steady state evolution in the upstream reach and a desequilibrium in the downstream reach.